Metode pengelolaan sampah medis padat di masa pandemi: sebuah tinjauan literatur - Balqis Mira Firdausy (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Waste management is a crucial thing to do as a form of responsibility for protecting the environment. However, sometimes ignorant hands cannot be conditioned, so that waste management is often not optimal. Not to mention that during the Covid-19 pandemic, the current capacity for waste is not just ordinary waste, but now medical waste is also included in the list of waste that needs to be managed properly and appropriately. Knowing that medical waste has a tendency to transmit advanced disease, various forms of policies and strategies are carried out by the government and medical personnel so that the management of medical waste can be handled properly. This writing used a descriptive qualitative method. The sources used rely on electronic media such as journals or electronic official websites and related books. The results of this paper conclude that the Indonesian government is expected to provide a forum and make it easier for medical personnel and related parties to manage medical waste appropriately and according to standards.